Dairy sludge characteristics and its degradation during thermal treatment and thermal plasma treatment - Júnior, Pedro William Paiva Moreira; de Souza Miranda, Felipe [UNESP]; Prado, Eduardo Sant Ana Petraconi; Essiptchouk, Alexei Mikhailovich [UNESP]; Cruz, Antônio Carlos; Petraconi Filho, Gilberto (Taylor & Francis, 2024)
Thermal treatment and thermal plasma treatment processes of dairy sludge were conducted. The thermal treatment was undertaken at temperatures from 200 °C to 1000 °C to establish the chemical composition and thermal degradation of the sludge. These results served as a foundation for interpreting the properties of the vitreous slag obtained from the sludge treated in the DC-transferred arc plasma reactor. The dairy sludge is characterised by a high volatile matter but also presents substantial ash content, with primary elements such as Al, P, Si, Ca, and Fe. The characterisations of the samples were made employing techniques like X-ray fluorescence, X-ray diffraction analysis (XRD), FT-IR spectrometry, Thermogravimetric analysis, and Differential Scanning Calorimetry. The results highlight the degradation of primary milk components like lactose, casein protein, and milk fat, with distinct differential thermogravimetric peaks at 230, 316, and 479 °C. As the temperature of thermal treatments approached 1000°C, silicon dioxide, calcium silicon, dicalcium silicate, and hydroxyapatite were identified in XRD spectra. Plasma-treated sludge features various oxide crystalline structures, including Al2O3, CaO(Al2O3)6, CaO(Al2O3)2, Ca2Al(AlSi)O7, KFeO2, and ZrO1.98. FTIR analysis of sludge identifies a complex organic composition presenting alkanes, amines, amides, hydroxyl groups, and metallic and semi-metallic oxide bond absorption. The FTIR results suggest the degradation of organic compounds and retention of phosphorous and aluminum bonds, especially after 600 °C. The vitreous slag from plasma treatment exhibits distinct composition characteristics without organic compound, presenting a vitreous and metallic/ceramic matrix. This research underscores the potential of thermal plasma treatments to neutralise dairy sludge.
Keywords: dairy sludge; DC-transferred arc plasma‌; Thermal plasma; waste management; waste treatment